MENYELESAIKAN MASALAH DI ANTARA SESAMA ANGGOTA JEMAAT BERDASARKAN PETUNJUK YESUS DI MATIUS 18:15 - Gerry C.J. Takaria (Fakultas Filsafat Universitas Advent Indonesia, 2015)
Remind the mistakes of others is not an easy matter. Misunderstandingscan be occurring with one another, and peace became far from our lives; there will behatred, conflict, hurt, and others. Therefore, in reminding the mistakes of others, wemust have a strong foundation of truth, and everything must be based on love.Apostle Paul in his letter in Rome 13:10 “Love worked no ill to his neighbor:therefore love is the fulfilling of the law.” We will remind the mistakes of othersbecause we love it, not because you want to drop or criticizing. With reminded, thatperson may can be convert back to the right path and be saved.Jesus has given the appropriate steps in solving problems among God’speople, it is recorded in Matthew 18:5-17. The stages are as follows: Privateconversation (Matthew 18:15); The talk in front of a witness (Matthew 18:16); Thetalk in front of the Church (Matthew 18: 17a); Of view of him as a man who does notknow God (Matius18: 17b). The first step is to meet in person is the mostfundamental stage and it seems a simple, but is actually the most important steps inthe reconciliation process in solving problems.There are 5 things that are important in implementing the first step, namely:1. Let us treat the guilty as our brother, and not regard them as enemies; 2. When wecome to him, make sure that there is a problem that absolutely must be resolved; 3.Go in private or alone to those who are innocent, not representing it through others;4. Speak to him in the guidance of the Holy Spirit through the words humble andgentle spirit. Success in carrying out Jesus’ command, to speak to people who areguilty in a proper way, will bring blessings to ourselves, to guilty person and to thechurch of God.